Synthesis of novel substituted benzaldehyde (Hepta-O-acetyl-β-lactosyl)thiosemicarbazones - Duy, Le Hoang; Phung, Nguyen Kim Phi (Vietnam Journal of Chemistry, 2012)
A series of substituted benzaldehyde hepta-O-acetyl-b-lactosyl thiosemicarbazones were synthesized by condensation reactions of hepta-O-acetyl-b-lactosyl thiosemicarbazide with corresponding substituted benzaldehydes. Structures of thiosemicarbazones were confirmed by spectroscopic (IR, NMR) methods.